2017
DOI: 10.1128/jcm.02155-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Parasight Platform for Malaria Diagnosis

Abstract: The World Health Organization estimates that nearly 500 million malaria tests are performed annually. While microscopy and rapid diagnostic tests (RDTs) are the main diagnostic approaches, no single method is inexpensive, rapid, and highly accurate. Two recent studies from our group have demonstrated a prototype computer vision platform that meets those needs. Here we present the results from two clinical studies on the commercially available version of this technology, the Sight Diagnostics Parasight platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Microscopy Mixed 12 0 0 0 12 Negative 0 42 3 5 50 pf 0 0 10 0 10 pv 0 0 0 28 28 Total 12 42 13 33 0 0 6 Negative 3 42 5 12 62 pf 1 0 8 0 9 pv 2 0 0 21 23 Total 12 42 13 33 100 The Parasight digital cytometry-based scanning and detection system for malaria has shown promising results in previous studies. 10,11 We tested it for practical feasibility in terms of accuracy, cost effectiveness and rapidity. Our study has shown that in comparison to gold standard microscopy, the digital cytometry gave similar results (in terms of accurate species detection as well) when parasite concentration was on higher side (mean 0.0515%).…”
Section: Rapid Diagnostic Tests (Rdt) Vs Digital Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopy Mixed 12 0 0 0 12 Negative 0 42 3 5 50 pf 0 0 10 0 10 pv 0 0 0 28 28 Total 12 42 13 33 0 0 6 Negative 3 42 5 12 62 pf 1 0 8 0 9 pv 2 0 0 21 23 Total 12 42 13 33 100 The Parasight digital cytometry-based scanning and detection system for malaria has shown promising results in previous studies. 10,11 We tested it for practical feasibility in terms of accuracy, cost effectiveness and rapidity. Our study has shown that in comparison to gold standard microscopy, the digital cytometry gave similar results (in terms of accurate species detection as well) when parasite concentration was on higher side (mean 0.0515%).…”
Section: Rapid Diagnostic Tests (Rdt) Vs Digital Cytometrymentioning
confidence: 99%
“…At Apollo Hospital India, the device showed a Pearson correlation coefficient of 0.84, compared to microscopy (correlation coefficients of 0.98 for P. falciparum and 0.83 for P. vivax); at AKUH, the device showed a Pearson correlation coefficient of 0.85, compared to microscopy (correlation coefficients of 0.86 for P. falciparum and 0.55 for P. vivax). 10 In a study by Srivastava et al 2015 for comparison of parasite species detection by PCR and its comparison with digital cytometry. From samples found to be positive by both PCR and SightDx, SightDx speciated 73.3% of PCR P. falciparum + samples and 91.4% of PCR P. vivax + samples, as shown in Table 3.…”
Section: Rapid Diagnostic Tests (Rdt) Vs Digital Cytometrymentioning
confidence: 99%
“…The SYTO family of dyes also excelled in its capacity to stain cultured malaria positive red blood cells (RBCs). Additional fluorescent-based systems have used a dye combination to achieve accurate staining such as the Parasight system which makes use of multiple dyes in the 370 and 475 nm excitation imaging ranges ( 23 25 ).…”
Section: Sample Preparationmentioning
confidence: 99%
“…A platform designed by Vink et al using a live intra-vital cartridge stain is capable of analyzing 0.47 μL of blood, potentially analyzing 2.5 million RBCs, and yielding a projected LOD of 10 parasites/μL within 15 min ( 21 ). A second fluorescent system, the Parasight malaria detection device, showed an LOD of under 100 parasites/μL ( 25 ). Limits of detection on these devices should reduce with further algorithm development, though the LOD will eventually be limited by the noise floor caused by artifacts from film preparation and staining.…”
Section: Device Limit Of Detectionmentioning
confidence: 99%
“…Even these analysis are time consuming and leads to inaccuracy and inconsistency in some cases. The computerised approach uses digitized blood slides that will be able to improve the consistence in diagnosis [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%